BRAIN VITALITATION GYM BERPENGARUH TERHADAP FUNGSI KOGNITIF LANSIA - Utami, Rindu Febriyeni; Adenikheir, Annisa (PHYSIO MOVE JOURNAL, 2023)
As they get older, the elderly will experience a decline in several body functions, one of which is cognitive function. As the center of thinking power, the brain also requires care, namely by carrying out simple movements followed by various components of brain function such as vision, imagination, hearing and emotions. This can be done by doing a brain vitalization gym. The aim of this research is to determine the effect of the brain vitalitation gym in improving the cognitive function of the elderly. The design of this research is Quasi-experimental with a pretest-posttest one group design approach. The population in this study was all elderly people at the Biaro Community Health Center totaling 318 people, the sample in this study was 10 elderly people. The sampling technique was carried out by purposive sampling. Cognitive function was measured using the MMSE (Mini-Mental State Examination). The results showed that the average cognitive function before the brain vitalization gym intervention was 16.20 and after the intervention it was 23.10. The p value = 0.000 means that there is an increase in cognitive function after being given Brain Vitalitation Gym Keywords: Brain Vitalitation Gym, Cognitive Function, Elderly